FORMULASI, UJI ANTIOKSIDAN DAN ANTIBAKTERI SERUM GEL EKSTRAK KULIT PISANG KEPOK (Musa balbisiana) SEBAGAI ANTI- ACNE - Yuniarsih, Nia; Abriyani, Ermi; Shadrina, Alliza Nur (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
One skin problem that never goes away is acne, which is a skin disorder caused by excessive sebum production and can be caused by bacteria such as Propionibacterium acnes. Another factor causing acne is also due to the presence of free radicals. Compounds that can counteract free radicals are antioxidants. This study aims to determine the best formula and storage stability of serum gel of ethanol extract of kepok banana peel (Musa balbisiana) as antioxidant and antibacterial on Propionibacterium acnes bacteria. The study was in vitro with antibacterial activity test using the pitting method and antioxidant activity test using DPPH method. Serum gel preparations were made with three concentrations of kepok banana peel (Musa balbisiana) extract addition, namely formula F1 (5%), F2 (10%), and F3 (15%). Serum gel base was used as negative control and klindamisingel as positive control. This study found that kepok banana peel contains alkaloid, flavonoid, tannin and saponin compounds. Antibacterial activity has an inhibition zone against Propionibacterium acne bacteria at all three concentrations. Serum gel F1 has an inhibition zone of 12.51 ± 0.95, F2 has an inhibition zone of 17.26 ± 0.96, F3 24.08 ± 0.73. Antioxidant activity of serum gel of kepok banana peel (Musa balbisiana) showed IC50 F1 of 95.732 ppm, F2 of 51.368 ppm, F3 of 5.929 ppm. From this study, it can be concluded that serum gel Formula 3 containing 15% ethanol extract of kepok banana peel (Musa balbisiana) is the most effective formula against antibacterial and antioxidant activity.